Shame on the brain: Neural correlates of moral injury event recall in posttraumatic stress disorder. Issue 6 (28th December 2020) - Lloyd, Chantelle S.; Nicholson, Andrew A.; Densmore, Maria; Théberge, Jean; Neufeld, Richard W. J.; Jetly, Rakesh; McKinnon, Margaret C.; Lanius, Ruth A.
Abstract: Background: Moral injury (MI) is consistently associated with adverse mental health outcomes, including the development of posttraumatic stress disorder (PTSD) and suicidality. Methods: We investigated neural activation patterns associated with MI event recall using functional magnetic resonance imaging in participants with military and public safety‐related PTSD, relative to civilian MI‐exposed controls. Results: MI recall in the PTSD as compared to control group was associated with increased neural activation among salience network nodes involved in viscerosensory processing and hyperarousal (right posterior insula, dorsal anterior cingulate cortex; dACC), regions involved in defensive responding (left postcentral gyrus), and areas responsible for top‐down cognitive control of emotions (left dorsolateral prefrontal cortex; dlPFC). Within the PTSD group, measures of state and trait shame correlated negatively with activity among default mode network regions associated with self‐related processing and moral cognition (dorsomedial prefrontal cortex; dmPFC) and salience network regions associated with viscerosensory processing (left posterior insula), respectively. Conclusions: These findings suggest that MI event processing is altered in military and public safety‐related PTSD, relative to MI‐exposed controls. Here, it appears probable that as individuals with PTSD recall their MI event, they experience a surge of blame‐related processing of bodily sensations within salience network regions, including the right posterior insula and the dACC, which in turn, prompt regulatory strategies at the level of the left dlPFC aimed at increasing cognitive control and inhibiting emotional affect. These results are consistent with previous findings showing enhanced sensory processing and altered top‐down control in PTSD samples during autobiographical memory recall.